Analisis Implementasi Kurikulum Merdeka pada Pembelajaran IPAS di Kelas IV Sekolah Dasar Negeri 28 Pontianak Kota - Angela, Yuyun; Kartono, Kartono; Ghasya, Dyoty Auliya Vilda (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research aims to provide an analysis in the realm of planning, implementation and obstacles in the process of implementing an independent curriculum in teaching and learning activities in science or science subjects in class IV 28 Pontianak City Elementary School. This research uses qualitative research. The data collected was obtained through interviews, observation and documentation. The subjects in this research included class IV A teachers and class IV B teachers. Next, the data was analyzed using the Miles and Huberman technique through four stages, including the process of data collection, data reduction, data presentation, and drawing conclusions. Data validity testing was carried out using technical triangulation. This research resulted in a science and science learning planning process where an educator designs teaching modules that have been adapted to independent curriculum procedures which consist of three elements including general information, core components and attachments. In the process of implementing learning, educators have implemented a learning system based on the suitability of the learning flow available in the teaching module so that learning can be carried out based on the syntax of the learning model used. The obstacles felt by educators in the process of implementing their curriculum in natural science and natural science subjects in class IV include adapting material to learning objectives, time management in carrying out teaching and learning activities, and the availability of infrastructure, for example lack of internet or WiFi network facilities and projector.